Impact of voltage degradation in water electrolyzers on sustainability of synthetic natural gas production: Energy, economic, and environmental analysis. (1st October 2021) - Lim, Dongjun; Lee, Boreum; Lee, Hyunjun; Byun, Manhee; Cho, Hyun-Seok; Cho, Wonchul; Kim, Chang-Hee; Brigljević, Boris; Lim, Hankwon
Highlights: Perform 3E analysis for sustainable SNG production process with different WEs. Investigate quantitative impact of voltage degradation on SNG production. Analyze carbon footprint for SNG production with different electricity sources. Abstract: Synthetic natural gas (SNG) production from captured CO2 and H2 produced by water electrolysis using renewable energy is of increasing interest for low-carbon fuel production, CO2 utilization technology, and unstable renewable energy storage. In this study, the effect of voltage degradation in a water electrolyzer, a core technology for SNG production, on the unit production cost of SNG production and CO2 emissions, with different water electrolysis types such as alkaline electrolysis (AEL), proton exchange membrane electrolysis (PEMEL), and solid oxide electrolysis (SOEL), was identified through techno-economic and environmental assessment. In particular, the energy efficiency, unit production cost of SNG, and CO2 emissions were identified based on the change in the power consumption caused by voltage degradation. Moderate voltage loss results in a decrease in energy efficiency from 53.8% to 48.8% in AEL, 55.3% to 47.0% in PEMEL, and 76.3% to 51.2% in SOEL. Moreover, respective SNG unit production costs of 140.3–170.2 USD MWh −1, 157.5–203.1 USD MWh −1, and 153.1–353.5 USD MWh −1 for AEL, PEMEL, and SOEL, respectively, were obtained, showing an increase in SNG production cost due to the voltage degradation. Furthermore, total CO2 emissions for the SNG production process were investigated considering voltage degradation as well as electricity generation sources.